The Efficiency Capture on Friendly Modification Boat Seine in Kendal District, Central Java - Fitri, Aristi Dian Purnama; Asriyanto, Asriyanto; Setiyanto, Indradi; Kurohman, Faik (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2011)
Boat seine is fishing gear in coastal areas consisting of wings and cod (bag). Target catch seine boat in the waters of Spring Sikucing-Weleri was rebon (shrimp) and fish. Boat seine problems that exist due to the large hydrostatic pressure, the number of crew (ABK) and size of a lot of fish are juvenile (<10 cm TL). Aimed of modification boat seine at improving the technical efficiency of fishing that will affect the increased welfare of fishermen, as well as making environmentally-friendly fishing gear.Modification of the boat seine was located on the wing with nylon netting material change to 380 d / 9, and 7 mm mesh size. Number of crew (ABK) during hauling into 6-8 people, not the garbage that carried during the arrest operation, and the catch of fish is not juvenile (> 15 cm TL). Keywords: Boat seine modification, Effective, Efficiency and Selective